2021
DOI: 10.1021/acsagscitech.0c00070
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of DNA Methylation Caused by Cold Plasma Treatment Restore Delayed Germination of Heat-Stressed Rice (Oryza sativa L.) Seeds

Abstract: In rice (Oryza sativa L.), seeds exposed to heat stress during grain filling exhibit delayed germination because of DNA methylation levels at promoters of abscisic acid (ABA, a germination-inhibiting hormone) catabolism genes and α-amylase (starch-hydrolyzing enzyme) genes, affecting their expression levels. Cold atmospheric plasma is known as an innovative and sustainable energy that has positive effects on the growth and development of many plant species. We, therefore, treated seeds that matured under heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 22 publications
(38 reference statements)
0
27
0
Order By: Relevance
“…It has been recognized that seed treatment with CP induces numerous adaptive changes observable in the growing plants (see the most recent reviews [23][24][25][26][27][28][29]). Seed treatment with CP results in chemical modifications in seed coat leading to increased surface wettability [55], increased seed electron paramagnetic resonance (EPR) signal [33,56,57], rapid changes in the balance of phytohormones [34,35,58,59] and DNA methylation in dry seeds [60] resulting in changes of protein expression and enzymatic activities underlying the effects on germination. The systematic response of plants and seeds to EMF treatment has been reviewed recently [25].…”
Section: Discussionmentioning
confidence: 99%
“…It has been recognized that seed treatment with CP induces numerous adaptive changes observable in the growing plants (see the most recent reviews [23][24][25][26][27][28][29]). Seed treatment with CP results in chemical modifications in seed coat leading to increased surface wettability [55], increased seed electron paramagnetic resonance (EPR) signal [33,56,57], rapid changes in the balance of phytohormones [34,35,58,59] and DNA methylation in dry seeds [60] resulting in changes of protein expression and enzymatic activities underlying the effects on germination. The systematic response of plants and seeds to EMF treatment has been reviewed recently [25].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma-treated seed revealed the enhanced superoxide dismutase and Ascorbate peroxidases' (APXs') activities. [109] Recently, heat-stressed Rice (Oryza sativa) seeds treated with Air-scalar DBD plasma with 2.17-W discharge power showed a higher germination rate than without plasma heatstressed seeds throughout the germination time course [65]. Rice seeds with low-pressure (~1333 Pa) DBD plasma working with Ar + Air gas mixture [66], hybrid cold plasma (HCP) with Ar feed gas [67], and Air-atmospheric pressure multi-pin plasma generator [68] showed an increase in seed germination and germination rate.…”
Section: Maize (Zea Mays)mentioning
confidence: 99%
“…Several studies have demonstrated that ROS and RNS, especially the interaction between the two, are essential for the plant acclimatisation to high and low temperatures [202,203]. Recently, plasma treatment was shown capable of considerably improving the germination of rice seeds affected by heat stress through epigenetic regulation [204].…”
Section: Rons Involvement Under Abiotic Stress Conditionsmentioning
confidence: 99%